Keefektifan Strategi Visual Dalam Pembelajaran Keterampilan Sosial Pada Anak Dengan Kondisi Spektrum Autis Tipe Sindroma Asperger (ASD) - Wawan Ridwan Mutaqin (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Visual Strategy, Learning Social Skills, Autis Spectrum Disorder (ASD. Tantrum behavior is a behavior that often appears in children with autism spectrum, in the form of behavioral tantrums, anger outbursts, screams, cries, banging his head, banging, kicking, rolling and rigidity of the body. It often makes teachers and parents are confused about it. Usually teachers or parents are always trying to explain verbally to the child, but the results, the child remains tantrums if it wishes to buy food or toys when school is not met. This study aims to determine the effectiveness of the application of visual strategies to address the tantrum behavior in children with autism condition Spectrum Disorder (ASD). This research is a qualitative descriptive analysis. Sampling was done by sampling techniques with specific criteria (purposive sampling). Informants in this study is a teacher assistant (shadow teacher), parents and classroom teachers. The results showed that (1) the planning of learning social skills with visual strategy was well planned but the system documentation is still general, (2) the implementation of learning social skills with visual strategy done in the classroom and outside the classroom, using the drawings concerning a actions to be performed by children, (3) evaluation of learning social skills with visual strategies have been implemented during the learning process and at the end of the study, but has not been well documented, (4) the use of visual strategies in learning social skills in children ASD types Asperger syndrome rated very effective views of a significant change in behavior before and after learning social skills with visual strategy. The implications of this study that the TPP Al-Firdaus need to use visual strategies in learning social skills in autistic children and improve the quality of teachers and therapists to use visual strategies for learning and therapy for children with autism more optimal.